Role of reflectance confocal microscopy for in vivo investigation of oral disorders: White, red and pigmented lesions. Issue 5 (20th March 2023) - Franceschini, Chiara; Mandel, Victor Desmond; Peterson, Gary; Manciocco, Valentina; Guitera, Pascale; Rajadhyaksha, Milind; Ardigò, Marco
Abstract: In vivo reflectance confocal microscopy (RCM) is poorly investigated in oral pathology due to the peculiar anatomical and topographical oral mucosa features. A dedicated handheld confocal microscope with an intra‐oral probe was developed for oral mucosa imaging. The main objective was to describe the healthy oral mucosa and the cytoarchitectural findings detectable in different oral disorders by means of the newly designed handheld confocal microscope. Secondary aim was to identify the main RCM criteria that differentiate oral lesions in order to provide algorithm for a rapid non‐invasive evaluation. This observational retrospective study included all consecutive patients with oral disorders and volunteers with healthy oral mucosa who underwent RCM examination in our outpatient clinic from September 2018 to December 2021. Three different investigators examined together the RCM images to detect the key features and secondary criteria for each type of oral lesion collected. The study population included 110 patients affected by oral lesions and seven volunteers with healthy oral mucosae. A total of 15 oral disorders were imaged and divided in three main groups: white, red and pigmented lesions. Key features and secondary criteria were identified for every single type of oral disease. RCM permits a cytoarchitectural evaluation of the oral mucosae affected by inflammatory, dysplastic and neoplastic diseases, thus orienting the clinicians towards non‐invasive diagnosis and enhancing the diagnostic management. The "tree diagrams" proposed allow a schematic and simplified view of confocal features for each type of oral disease, thus drastically reducing the diagnostic timing.